Le vocabulaire de guerre dans la traduction des Bienveillantes de J. Littell vers le slovene - Schlamberger Brezar, Mojca (Linguistica (Ljubljana), 2018)
Military vocabulary and the vocabulary of war are part of specialized as well as general lexicon. Such language was present in Slovene even before the creation of the Slovene army in 1991. In this context the systematic development of military terminology was left to enthusiastic individuals. Due to the lack of terminological reference works, the creation of military vocabulary was in the hands of people who experienced military service and war, as well as writers and translators. But can lite-rature present a reliable source for terminological research? We also try to answer this question.Our research is focused on the lexis concerning war, the denomination of mi-litary functions and ideologies in the context of the Second World War as they appear in the French original and Slovene translation of Bienveillantes (The Kindly Ones) by J. Littell (2006, 2010). Its war lexis is compared to that of some Slovene original works and translations concerning the Second World War. In addition, the monolingual corpus Gigafida is taken into account and the question of the (in)stability of prescriptive norms of Slovene is discussed.
Keywords: francoščina; književno prevajanje; Littell, Jonathan: Sojenice; slovenščina; svetovna vojna 1939-1945; vojni besednjak